2017
DOI: 10.1111/ajgw.12263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intensity of post-veraison defoliation or shoot trimming on vine physiology, yield components, berry and wine composition in Aglianico grapevines

Abstract: Background and Aims: Post-veraison trimming and defoliation have been proposed as strategies to decrease the concentration of berry carbohydrate at harvest and of wine alcohol, but it is unclear which of these two pruning techniques is more suitable and at what intensity they should be applied. The aimof this 3-year study was to compare the suitability of two intensities of post-veraison trimming or defoliation in controlling sugar accumulation in the berries of Aglianico grapevines.\ud Methods and Results: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 57 publications
8
16
0
Order By: Relevance
“…Berries from defoliated vines presented TA values no different from the control in 2015, whereas it was lower in 2017. Previous studies conducted on red grape cultivars (Sangiovese, Ciliegiolo, Barbera, Aglianico) in different cultivation environments, reported similar effect of pre and post-veraison sprays with antitranspirant on sugar accumulation in the berries [10,12,14,16]. Our findings therefore confirmed, for the first time, the efficacy of the antitranspirant compounds for the control of sugar accumulation in an early-ripening white cultivar such as Sauvignon blanc.…”
Section: Berry Ripening Dynamic and Compositionsupporting
confidence: 86%
See 1 more Smart Citation
“…Berries from defoliated vines presented TA values no different from the control in 2015, whereas it was lower in 2017. Previous studies conducted on red grape cultivars (Sangiovese, Ciliegiolo, Barbera, Aglianico) in different cultivation environments, reported similar effect of pre and post-veraison sprays with antitranspirant on sugar accumulation in the berries [10,12,14,16]. Our findings therefore confirmed, for the first time, the efficacy of the antitranspirant compounds for the control of sugar accumulation in an early-ripening white cultivar such as Sauvignon blanc.…”
Section: Berry Ripening Dynamic and Compositionsupporting
confidence: 86%
“…In this respect, the mechanisms underlying the effect of antitranspirant compounds on berry acidity should receive more targeted research, focusing also on the fate of the two main organic acids (malic and tartaric) in the grape berry. Finally, as in other studies [12,16] a postveraison reduction of the canopy area obtained by manually pulling the leaves close to the fruiting zone was found able to delay sugar accumulation in Sauvignon blanc berries with only minor modification of their final titratable acidity.…”
Section: Berry Ripening Dynamic and Compositionsupporting
confidence: 81%
“…42 showed that veraison is the most sensitive stage for anthocyanin accumulation in the berry skins of Aki Queen and that low average temperature treatment (20 vs 30 °C) during veraison significantly enhanced anthocyanin accumulation via an increase in mRNA levels of anthocyanin biosynthetic genes. Furthermore, exogenous treatments with abscisic acid 66 or agronomic practices, such as the application of different deficit irrigation regimes 67 , removal of apical leaves 68 , 69 or shoot trimming 70 don’t imply a variation in skin anthocyanin accumulation if conducted in post-veraison. According to our results, it appears clear that the possibility of influencing anthocyanin biosynthesis at transcriptional level by low night temperature is limited to the veraison stage and that subsequently no positive effects may arise.…”
Section: Discussionmentioning
confidence: 99%
“…Two-year-old shoots (holding the production of the year) per plant were selected to monitor growth by recording shoot length, number of leaves and leaf area. Leaf area was estimated by measuring the lamina width and applying the equations calculated based on the measurement of width and area of 25 leaves per treatment by means of a electronic leaf area meter (LI-3100 model, LI-COR Inc., Lincoln, Nebraska, United States), according to Caccavello et al (2017).…”
Section: Biometric Analyses and Yieldmentioning
confidence: 99%